COMMUNICATION STRATEGY IN MARKETING 5.0 ON PURCHASE DECISION IN THE MARKETPLACE TOKOPEDIA - Jufriadi Jufriadi; Muhammad Syafii Basalamah; Amir Mahmud; Imaduddin Imaduddin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2022)
This research aims is to find out the effect of communication and marketing 5.0 strategies on purchase decisions in the Tokopedia marketplace. This study uses quantitative research with a total of 88 respondents with predetermined criteria. Data analysis was performed using multiple linear regression analysis processed with SPSS. Based on the results of the research conducted, it shows that the communication strategy has no effect on purchase decisions and Marketing 5.0 has an influence on Purchase Decisions.